Evaluation of Cottontail Pellets Collected in Suboptimal Conditions for DNA Analysis - Christopher M. Whipps; Amanda E. Cheeseman; K. Alice Lindsay; Jonathan B. Cohen (Wildlife Society Bulletin)
ABSTRACT Occupancy monitoring of the New England cottontail (Sylvilagus transitionalis) relies on collections of fecal pellets made following a snowfall, and subsequent genetic screening to distinguish New England cottontail pellets from those of the eastern cottontail (S. floridanus) and snowshoe hare (Lepus americanus). In years when snowy conditions are not common, less frequent sampling may result in data gaps at long‐term monitoring sites, and jeopardize ongoing field research projects that rely on genetic data from fecal pellets. Such conditions occurred in the lower Hudson Valley, New York, USA, in the winter of 2015–2016, during which we collected pellets from the ground to evaluate performance of genetic testing relative to pellet quality. Pellets were categorized on overall appearance of degradation, assigned a pellet quality score, and then genetically analyzed to identify species using mitochondrial DNA. The pellets identified as being from New England cottontail were further evaluated targeting nuclear microsatellite DNA to obtain a multilocus genotype to identify individual rabbits. Species identification was possible for 89% of the highest quality pellets from the ground, and 68% in the most degraded pellets. A complete multilocus genotype was obtained in 79% of the least degraded pellets, but only 14% of the most degraded pellets. Certain genetic loci strongly influenced this success rate, with some performing better than others. Pellets collected from snow were still most reliable with 100% identified to species, and >97% of New England cottontail with a complete multilocus genotype. Thus, if researchers are genotyping rabbit pellets for applications such as abundance estimations, only the higher quality pellets from the ground or those collected from snow will likely be useful. For occupancy monitoring, a wider range of pellets may be acceptable for species identification, with the understanding that there is a tradeoff with pellet quality and successful DNA analysis. These results indicate that sampling from the ground and qualitative assessment of pellet quality using our categorization scheme is a viable method for New England cottontail monitoring in years with less snow. © 2020 The Wildlife Society.